Kerugian Konsumen Akibat Penggunaan Bahan Bakar Minyak Pertalite Di Bawah Standarisasi dalam Perspektif Keadilan - Ni Putu Sintiya Puspitasari; Bagus Gede Ari Rama; Anak Agung Ayu Ngurah Sri Rahayu Gorda; Ketut Elly Sutrisni (LOCUS MEDIA PUBLISHING, 2025)
The increase in the number of vehicles in Indonesia shows that there is a dynamic growth of public transportation in line with economic development. This growth requires more efficient fuel distribution management so that people's energy needs can be met according to standardization. The problem arose when Pertalite fuel allegedly caused damage to the engine of the consumer's vehicle, so the consumer demanded compensation. The purpose of this study is to analyze the form of consumer losses and legal remedies in the perspective of justice. This research uses normative research methods based on primary and secondary legal sources, as well as legislative, factual, and conceptual approaches. The results of this study confirm that losses experienced by consumers include technical, economic, and social aspects, as well as weak business actors' accountability. ha katas Compensation, the realization of compensation by business actors has not run optimally. Legal remedies can be pursued through litigation and non-litigation through BPSK which is faster and more efficient, but the challenge of proving it is an obstacle. The principle of corrective justice according to Aristotle emphasizes the importance of reparation for losses in proportion. To ensure substantive justice, the state needs to strengthen oversight and improve access to information for consumers.